EDUKASI KEBERMANFAATAN UMKM UNTUK PENINGKATAN PEREKONOMIAN MASYARAKAT DI KELURAHAN TINGGAR - Zahra, Surti; Kusumawati, Nugrahini; Sumiarsih, Cicih; Rokhiyawati, Lilis; Nurhasanah, Nurhasanah; Kusuma, Jaka Wijaya (Gapenas Publisher, 2024)
Micro, Small and Medium Enterprises (MSMEs) are one of the drivers of the economy whose existence is very reliable and highly calculated. MSMEs contribute to the Indonesian economy, especially for the people of Tinggar Village, Curug District. In addition to being able to improve the family economy and also open new jobs, there are many problems faced by the community in opening a business, especially in terms of capital and marketing strategies. The PKM team group 7 from the Faculty of Economics and Business, Bina Bangsa University was moved to carry out a Seminal Education Activity on the Benefits of MSMEs with the title